2006
DOI: 10.1002/app.22905
|View full text |Cite
|
Sign up to set email alerts
|

The shear strength of Calabrian pine (Pinus brutia Ten.) bonded with polyurethane and polyvinyl acetate adhesives

Abstract: ABSTRACT:In this study, the change in shear strength on radial and tangential surfaces of Calabrian Pine (Pinus brutia Ten.) wood having different roughness values as the result of sawing with a circular ripsaw, planing and sanding, and bonded with polyurethane (PU) and polyvinyl acetate (PVAc) adhesives at the pressure levels of 3, 6, and 9 kgf/ cm 2 , was studied. Each of the 360 specimens prepared to determine the effect of the variables on bond performance were subjected to shear test in an universal test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
3
11
0
1
Order By: Relevance
“…Results were found in the literature that shows that surface roughness affects bonding strength. This study showed results similar to the literature (Burdurlu et al 2006;Yang et al 2012;Knorz et al 2015;Kılıç 2016).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Results were found in the literature that shows that surface roughness affects bonding strength. This study showed results similar to the literature (Burdurlu et al 2006;Yang et al 2012;Knorz et al 2015;Kılıç 2016).…”
Section: Resultssupporting
confidence: 92%
“…The first group displayed the highest bonding strength (7.38 N/mm 2 ) from the aspect of surface roughness; this was followed by the second group (6.57 N/mm 2 ), and finally the third group (5.89 N/mm 2 ). Similar results were determined in the study of Burdurlu et al 2006. The PVAc adhesive produces higher shear strength values compared with the PU adhesive.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The roughness values of the tangentially cut surfaces were determined to be lower than the radially cut surfaces. Burdurlu et al (2006) have also determined that the Ra values of tangentially cut samples of red pine trees were lower than the values of radially cut surfaces. In the same manner, the Ra values of surfaces processed with the thickness machine were found to be lower compared to surfaces sanded with no: 80 sandpaper ( Table 5).…”
mentioning
confidence: 95%